The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/mma.5072
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear problem for the Laplace equation with a degenerating Robin condition

Abstract: We investigate the behavior of the solutions of a mixed problem for the Laplace equation in a domain Ω. On a part of the boundary ∂Ω, we consider a Neumann condition, whereas in another part, we consider a nonlinear Robin condition, which depends on a positive parameter δ in such a way that for δ = 0 it degenerates into a Neumann condition. For δ small and positive, we prove that the boundary value problem has a solution u(δ,·). We describe what happens to u(δ,·) as δ→0 by means of representation formulas in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(30 citation statements)
references
References 34 publications
(62 reference statements)
0
24
0
Order By: Relevance
“…Dalla Riva and Mishuris [17] have investigated the solvability of a small nonlinear perturbation of a homogeneous linear transmission problem by potential theoretical techniques. The present paper represents a continuation of the analysis done in [49], where the authors of the present paper have considered the behavior as δ → 0 of the solutions to the boundary value problem…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Dalla Riva and Mishuris [17] have investigated the solvability of a small nonlinear perturbation of a homogeneous linear transmission problem by potential theoretical techniques. The present paper represents a continuation of the analysis done in [49], where the authors of the present paper have considered the behavior as δ → 0 of the solutions to the boundary value problem…”
Section: Introductionmentioning
confidence: 98%
“…As is well known, the Neumann problem above may have infinite solutions or no solutions, depending on compatibility conditions on the Neumann datum. In [49], we have proved that, under suitable assumptions, solutions to (1) exist and we have shown that they diverge if the compatibility condition on the Neumann datum for the existence of solutions to (2) does not hold. In [49], we have considered a Robin problem as simplified model for the transmission problem for a composite domain with imperfect (nonnatural) conditions along the joint boundary.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations